Pelestarian Daya Tarik Pura Uluwatu Setelah Pandemi Covid 19 - Gagih Pradini; Dipa Teruna Awaloedin; Anisa Putri Kusumaningrum; Putri Aulia Ardani; Alisya Nur Insani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study discusses the preservation of the attractiveness of the Uluwatu Temple, which is located in the Pecatu Traditional Village, South Kuta District, Badung Regency, after a pandemic that paralyzed the tourism sector for approximately 2 years. The COVID- 19 pandemic has greatly impacted the Indonesian economy and especially the Bali tourism sector. The decline in local tourists and foreign tourists who come to tourist destinations in Bali. With this, the tourism sector in Bali loses a source of income. The purpose of this research is to find out what causes Uluwatu Temple to bounce back after the covid-19 pandemic and how to preserve tourist attractions at Uluwatu Temple.